Comprehensive analysis of tar reduction method in biomass gasification for clean energy production: A Review - Prasetiyo, Dani Hari Tunggal; Sanata, Andi; Sholahuddin, Imam; Nashrullah, Muhammad Dimyati; Nanlohy, Hendry Y.; Panithasan, Mebin Samuel (Universitas Muhammadiyah Magelang, 2024)
Biomass gasification is a promising renewable energy technology for the production of synthetic gas (syngas), consisting of hydrogen (H₂), carbon monoxide (CO), and methane (CH₄). This technology's primary challenge is tar formation – a heavy hydrocarbon compound that can block equipment, poison catalysts, and deteriorate syngas quality. Therefore, this study aimed to examine different tar reduction methods to support clean energy production through biomass gasification. To achieve this aim, two main approaches were adopted and the first was in-situ, focusing on modifying gasifier design and adjusting operational parameters. The second was ex-situ, which included catalytic reforming, thermal cracking, and plasma technology. The analysis also assessed different catalysts, such as biochar, and dolomite, as well as nickel- and iron-based materials, comparing their efficiency, sustainability, and economic viability. Several key factors influenced tar formation and reduction, namely feedstock type, operating temperature, air ratio, and reactor configuration. The result showed that combining in-situ and ex-situ technologies had substantial potential to significantly reduce tar, improve syngas quality, and optimize system performance. However, some challenges observed were reduced catalyst efficiency, high energy costs, and the need for more sustainable technologies. To improve the performance of gasification systems, this study provided information on catalyst development, operational parameter optimization, and plasma technology integration. Finally, the analysis provided a scientific basis and strategic recommendations to overcome tar problems and encourage the commercial use of biomass gasification towards a clean energy transition.